2016
DOI: 10.3928/01484834-20160516-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Criteria for Nursing Student Application of Evidence-Based Practice: A Delphi Study

Abstract: A baccalaureate program curriculum requiring the use of Bostwick's EBP Core Clinical Evaluation Criteria will provide a clear definition for understanding basic core EBP competence as expected for the assessment of student learning. [J Nurs Educ. 2016;55(5):336-341.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Indeed, learning outcomes appear more effective if the teaching strategies are connected to clinical practice [ 42 ]. This notion was emphasised in the core clinical evaluation criteria developed in the Delphi Study by Bostwick and Linden [ 43 ]. In contrast, Ilic and Maloney [ 44 ] found no difference in learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, learning outcomes appear more effective if the teaching strategies are connected to clinical practice [ 42 ]. This notion was emphasised in the core clinical evaluation criteria developed in the Delphi Study by Bostwick and Linden [ 43 ]. In contrast, Ilic and Maloney [ 44 ] found no difference in learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study sample is representative of this subset of family caregivers whose loved ones tell their illness stories on social media. There is no universal agreement on the proper size of the expert panel for Delphi methods; however, panels have ranged in size from 4 to more than 3000 participants [ 25 , 26 ]. Regardless of the large range of sample sizes in research studies, 5-10 experts are suggested [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Delphi method was used to guide the faculty and student focus groups as it is well suited to build consensus on a topic, utilizing a panel of experts to discuss and/ or expand on data collected from other data collection methods such as questionnaires or surveys (Bostwick & Linden, 2016). Developed in the 1950s and still widely utilized today, the goal of the Delphi method is to reduce the range of responses provided by participants and arrive at something closer to expert consensus (Bostwick & Linden, 2016). In this case, it was used to help identifying specific examples of troublesome mental health nursing knowledge from both the student and faculty perspectives.…”
Section: Methods and Proceduresmentioning
confidence: 99%